2021
DOI: 10.37304/jem.v2i1.2658
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh disiplin dan budaya kerja terhadap kinerja ASN melalui motivasi kerja Satpol PP Provinsi Kalimantan Tengah

Abstract: Penelitian ini bertujuan untuk mengukur pengaruh disiplin dan budaya kerja terhadap kinerja PNS melalui motivasi kerja Satpol PP Provinsi Kalimantan Tengah. Sebanyak 48 responden anggota Satpol PP di Provinsi Kalimantan Tengah dipilih dengan menggunakan purposive sampling. Data dikumpulkan dengan menggunakan kuesioner. Data yang diperoleh dianalisis dan hipotesis diuji menggunakan teknik analisis PLS (Partial Least Square) dengan software SmartPLS. Hasil penelitian menunjukkan bahwa pertama, Disiplin, Budaya K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…The results of this test show that the second hypothesis (H2) is accepted, which states that work motivation has a positive and significant effect on employee performance. The results of this research are in line with research conducted by [7] stating that work motivation has a positive and significant influence on employee performance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this test show that the second hypothesis (H2) is accepted, which states that work motivation has a positive and significant effect on employee performance. The results of this research are in line with research conducted by [7] stating that work motivation has a positive and significant influence on employee performance.…”
Section: Discussionsupporting
confidence: 89%
“…If individuals have a positive perception, they will consider work motivation as a challenge at work so that employees are more serious about doing their work and produce something that is useful for the employee or at the Gianyar Regency Civil Service Police Unit Office. [7] explains that work motivation has a positive and significant effect on employee performance. Another previous research conducted by [8] shows that work motivation has a positive and significant effect on employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…When Work Discipline increases, Work Motivation also increases. The results of this research are in line with research results from Siagian (2017);and Hutajulu (2021), where the results are that Work Discipline has a significant positive effect on Work Motivation.…”
Section: Testing the Accuracy Of The Research Modelsupporting
confidence: 90%
“…Research conducted by Siagian (2017) found the results that work discipline has a significant influence on work motivation in the Lubuk Baja Batam District Government Office. Likewise, research conducted by Hutajulu (2021) states that discipline has a direct positive effect on work motivation in the Central Kalimantan Province Satpol PP. Based on this statement, the following research hypothesis can be formulated: H3: Work Discipline has a significant positive effect on Work Motivation Work Culture Nawawi in Adha (2019) states that work culture is a habit that is carried out repeatedly by employees in an organization.…”
Section: Work Disciplinementioning
confidence: 99%
“…Satpol PP Kabupaten Sumbawa Barat Faktor yang menjadi kekuatan (S) dan Peluang (O) Satuan Polisi Pamong Praja seperti yang diungkapkan dalam tabel diatas sesuai dengan pendapat yang dikemukakan oleh Syarifuddin menitikberatkan kemampuan personil Satpol-pp dalam menjalankan perannya berdampak pada terwujudnya kondisi lingkungan yang nyaman, kondusif dan harmonis (Hutajulu, et al, 2021). Hasil Analisis SWOT menunjukkan bahwa yang menjadi faktor kekuatan organisasi adalah tingkat pendidikan personil, adanya pembinaan internal, dan tersedianya personil yang memiliki keterampilan yang dibutuhkan organisasi.…”
Section: Tabel 1 Faktor-faktor Yang Mempengaruhi Profesionalismeunclassified